BAC-BROWSER: The Tool for Visualization and Analysis of Prokaryotic Genomes - Garanina, Irina A.; Fisunov, Gleb Y.; Govorun, Vadim M. (Frontiers in Microbiology, 2018)
Prokaryotes are actively studied objects in the scope of genomic regulation. Microbiologists need special tools for complex analysis of data to study and identification of regulatory mechanism in bacteria and archaea. We developed a tool BAC-BROWSER, specifically for visualization and analysis of small prokaryotic genomes. BAC-BROWSER provides tools for different types of analysis to study a wide set of regulatory mechanisms of prokaryotes: - transcriptional regulation by transcription factors (TFs), analysis of TFs, their targets, and binding sites - other regulatory motifs, promoters, terminators and ribosome binding sites - transcriptional regulation by variation of operon structure, alternative starts or ends of transcription - non-coding RNAs, antisense RNAs - RNA secondary structure, riboswitches - GC content, GC skew, codon usage BAC-browser incorporated free programs accelerating the verification of obtained results: primer design and oligocalculator, vector visualization, the tool for synthetic gene construction. The program is designed for Windows operating system and freely available for download in http://smdb.rcpcm.org/tools/index.html.